Pengaruh Ekstrak Lengkuas Merah (Alpinia Galanga) Dosis Bertingkat Terhadap Ekspresi Caspase 3 dan Grading Kanker Payudara Mencit C3H - Vega Karlowee; Tjahjono Tjahjono; Noor Wijayahadi (MEDIA MEDIKA INDONESIANA, 2010)
Effect of oral administered graded doses of alpinia galanga on the caspase 3 expression and histopathological grading of breast cancer in C3H miceBackground: 1’-Acetoxychavicol Acetate (ACA), in Alpinia galanga, known to have pro apoptotic and anticancer effects. The pro apoptotic effect is by elevating caspase 8 and 9 activity. ACA causes the cycle cell stops at G0/G1 phase. The aim of this study is to prove the effect on caspase 3 and histopathological grading of breast cancer.Method: It was an laboratory experimental with post test only control group design. Four groups of C3H mice, aged 2-3 months, had breast cancer inoculation. After the tumor mass were palpabled, K received no extract, P1, P2, P3 received Alpinia galanga extract at dose levels of 225, 450, 750 mg/kgBW/day, for 2 weeks. Immunohistochemistry examination of caspase 3 expression was scored with Allred criteria and cancer grading was scored with modified Scarff-Bloom-Richardson (MSBR) criteria. All data were analyzed by Kruskal-Wallis test, with level of significant α <0.05.Result: At P1, P2, P3 there were 1, 5, 7 mice dead in each group before termination, while in K all were survived. Pro protocol analysis showed no significance difference on caspase 3 expression (p=0.137) and grading score (p=0.399) between groups. Intention to treat analysis showed significance differences on caspase 3 expression between P1 with K (p=0.033) and P3 (p=0.005), and significance difference on grading score between P3 with K (p=0.002) and P1 (p=0.004). Histopathology examination showed damages on liver and kidney, especially in P3, which might be the mice’s cause of death.Conclusion: Caspase 3 expression is the highest at dose level of 225 mg/kgBW/day. Grading score is the lowest at dose level of 750 mg/kgBW/day.ABSTRAKLatar belakang: Senyawa 1’-Acetoxychavicol Acetate (ACA) dalam Alpinia galanga memiliki efek proapoptosis dan antikanker. Efek proapoptosis melalui aktivasi caspase 8 dan 9. ACA menyebabkan terhentinya siklus sel fase G0/G1. Tujuan penelititan ini adalah membuktikan adanya efek terhadap caspase 3 dan grading kanker payudara.Metode: Jenis penelitian eksperimental dengan desain post test only control group. Mencit C3H usia 2–3 bulan dibagi 4 kelompok, diinokulasi kanker payudara. Setelah tumbuh massa tumor, kontrol (K) tidak diberi perlakuan dan P1, P2, P3 diberi ekstrak Alpinia galanga dosis 225, 450, 750 mg/kgBB/hari selama 2 minggu. Penilaian ekspresi caspase 3 berdasarkan kriteria Allred dan grading kanker berdasarkan kriteria modified Scarff-Bloom-Richardson (MSBR). Dilakukan uji beda Kruskal-Wallis dengan tingkat kemaknaan α <0,05. Hasil: Pada P1, P2, P3, didapatkan kematian mencit sebanyak 1, 5, dan 7 ekor, sedangkan K tidak ada. Dalam pro protocol analysis, tidak ada perbedaan bermakna ekspresi caspase 3 (p=0,137) maupun grading kanker (p=0,399) antar kelompok. Pada intention to treat analysis ekspresi caspase 3, ada perbedaan bermakna antara P1 dengan K (p=0,033) dan P3 (p=0,005). Pada grading kanker payudara, ada perbedaan bermakna antara P3 dengan K (p=0,002) dan P1 (p=0,004). Pada histopatologis organ, ditemukan kerusakan hati dan ginjal, terutama pada P3, yang kemungkinan mengakibatkan kematian mencit.Kesimpulan: Skor ekspresi caspase 3 kanker payudara tertinggi didapatkan pada dosis 225 mg/kgBB/hari. Skor grading kanker payudara terendah didapatkan pada dosis 750 mg/kgBB/hari.